2017
DOI: 10.1097/bpo.0000000000001054
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Follow-up of Neonatal Brachial Plexopathy: Psychological and Physical Function in Adolescents and Young Adults

Abstract: Purpose: The prevalence of neonatal brachial plexus palsy (NBPP) has been increasing since the early 1980s. No known studies have examined long-term psychological health and quality of life (QOL) in young adults. The purpose of this study was to investigate the psychosocial and intellectual aspects of NBPP during adolescence into young adulthood. Methods: A total of 31 patients were enrolled in the adolescent group (16 to 18 y) and 25 in the young adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…2e7 In addition, children with NBPP are at risk for obesity and for developing psychological and behavioral problems. 8,9 To reduce the risk of NBPP, 3 national guidelines on shoulder dystocia recommend interventional exercises (ie, consisting variably of didactics, communication skills, simulation exercises with mannequins, reviewing the maneuvers to use, debriefing, and documentation) for all staff in the labor and delivery unit because it improves communication skills and reduces the incidence of NBPP associated with shoulder dystocia. 1,10,11 Some reports on the topic of simulated exercise suggest a reduction in the frequency of NBPP after the implementation of training.…”
Section: Introductionmentioning
confidence: 99%
“…2e7 In addition, children with NBPP are at risk for obesity and for developing psychological and behavioral problems. 8,9 To reduce the risk of NBPP, 3 national guidelines on shoulder dystocia recommend interventional exercises (ie, consisting variably of didactics, communication skills, simulation exercises with mannequins, reviewing the maneuvers to use, debriefing, and documentation) for all staff in the labor and delivery unit because it improves communication skills and reduces the incidence of NBPP associated with shoulder dystocia. 1,10,11 Some reports on the topic of simulated exercise suggest a reduction in the frequency of NBPP after the implementation of training.…”
Section: Introductionmentioning
confidence: 99%
“…Further, in their study, 34 44% of adolescent and 68% of the young adult group were overweight or obese. There was a positive correlation between increased weight, depression, and anxiety.…”
Section: Discussionmentioning
confidence: 84%
“…Butler et al . 34 recently reported that long term psychological health and quality of life in young adults with birth related plexus injury. Although these patients could adapt and participate in most activities, they showed persistent functional limitations and a higher rate of comorbid obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, the treatment of shoulder deformities for BPBI must be individualized to the patient’s current limitations, future goals, and potential for remodeling. In studies of adolescents and young adults, patients function within the normal range of psychiatric symptomatology, quality of life, and cognitive function 86,87 .…”
Section: Discussionmentioning
confidence: 99%